"A sweet smile": the modulatory role of emotion in how extrinsic factors influence taste evaluation. Issue 5 (4th July 2018) - Wang, Qian (Janice); Spence, Charles
ABSTRACT: It has recently been demonstrated that the reported tastes/flavours of food/beverages can be modulated by means of external visual and auditory stimuli such as typeface, shapes, and music. The present study was designed to assess the role of the emotional valence of the product-extrinsic stimuli in such crossmodal modulations of taste. Participants evaluated samples of mixed fruit juice whilst simultaneously being presented with auditory or visual stimuli having either positive or negative valence. The soundtracks had either been harmonised with consonant (positive valence) or dissonant (negative valence) musical intervals. The visual stimuli consisted of images of emotional faces from the International Affective Picture System (IAPS) with valence ratings matched to the soundtracks. Each juice sample was rated on two computer-based scales: One anchored with the words sour and sweet, while the other scale required hedonic ratings. Those participants who tasted the juice sample while presented with the positively-valenced stimuli rated the juice as tasting sweeter compared to negatively-valenced stimuli, regardless of whether the stimuli were visual or auditory. These results suggest that the emotional valence of food-extrinsic stimuli can play a role in shaping food flavour evaluation and liking.